Preventing Retinal Detachment: Where are We? Implications from Stickler Syndrome - Morris RE; Kuhn F; Sipos T (Clinical Ophthalmology, 2022)
Robert E Morris,1– 3 Ferenc Kuhn,2,4 Timothy Sipos1– 3 1Retina Specialists of Alabama, LLC, Birmingham, AL, USA; 2Helen Keller Foundation for Research and Education, Birmingham, AL, USA; 3Department of Ophthalmology, University of Alabama at Birmingham (UAB), Birmingham, AL, USA; 4Department of Ophthalmology, University of Pécs Medical School, Pécs, HungaryCorrespondence: Robert E Morris, Helen Keller Foundation for Research and Education, 2208 University Boulevard, Suite 101, Birmingham, AL, USA, 35233, Tel +1 205 936-0704, Email rmorris@rmeyes.comAbstract: Stickler syndrome, a rare inherited disease, carries a lifetime risk of rhegmatogenous retinal detachment (RRD) of up to 65%, higher than any other predisposing condition known. Both syndromic and non-syndromic eyes suffer RRD predominately from the same pathogenesis, vitreous tractional tears in the peripheral retina. Consequently, extraordinary publications in 2021– 2022, each reporting successful prevention of RRD in Stickler syndrome, using 360-degree (encircling) laser retinopexy, provide the first strong evidence upon which similar prophylaxis in non-syndromic eyes at high risk of RRD from peripheral retinal tears can confidently go forward.Keywords: retinal tear, retinal detachment, retinal detachment prevention, 360-degree laser retinopexy, stickler syndrome, encircling laser prophylaxis